Macroeconomics : a contemporary introduction : study guide - Swann, Michael J. (Nelson, 1994)
The art and science of economic analysis. Some tools of economic analysis. The market system. The economic actors. Introduction to macroeconomics. Measuring economic aggregates and thecircular flow of income...